Phaeohyphomycosis caused by Exophiala spinifera: an increasing disease in young females in mainland China? Two case reports and review of five cases reported from mainland China. Issue 3 (15th January 2015) - Wang, Le; Wang, Chong; Shen, Yongnian; Lv, Guixia; She, Xiaodong; Zeng, Rong; Ping, Zhan; Liu, Weida
Summary No more than 30 cases of phaeohyphomycosis caused by Exophiala spinifera have been reported up to now in English and Chinese literature over the past half century. Here, we reported two cases of phaeohyphomycosis caused by E. spinifera and reviewed all the five cases reported from mainland China. These two involved were both young female, one patient experiencing recurrence during pregnancy and the other developing multiple‐site infections without apparent immunodeficiency. The aetiological agents were both identified as E. spinifera by molecular analysis. Oral itraconazole was proved effective enough for the first patient, while the combination of itraconazole and terbinafine was needed for the second patient. It seems that infections due to E. spiniferais increasing in China mainland nowadays, usually involving young female.